Women’s customer trusts in hospital's inpatient services - Zubaedah, Cucu; Rufaidah, Popy; Aripin, Dudi; Tjahajawati, Sri (Padjadjaran Journal of Dentistry, 2019)
Introduction: Customer trust is a tribute to officers or institutions performances and sacrifices. In the health marketing system, the relationship among health workers, doctors, patients or health service users is essential. The declining of women’s health will have an impact on the overall life qualities of the community and eventually will decrease the Indonesian Human Development Index. The purpose of this research was to analyze the customer trust of women’s inpatient in hospitals at West Java and determine the most influential dimensions and indicators of the women’s inpatient customer trust. Methods: This research was explanatory research conducted with the survey method with the sample size of 398 respondents. The unit of analysis was a hospital in West Java, while the observation unit was the inpatient community group which considers inadequate and gets health financing subsidies from the government in 42 hospitals from 28 cities or regencies in the West Java provinces. The sampling method was multistage sampling and the research tool was a questionnaire. Customer trust variable had two dimensions: honesty and benevolence; each with five indicators. The statistical analysis method used in this research was the Wilcoxon test and partial least square test. Results: Both dimensions were dominant in measuring the customer trust variables with loading factor values which relatively similar to 0.831 for benevolence and 0.831 for honesty. Hospital staff as a dominant indicator of benevolence, given the loading factor value at 0.819 and R2 value at 0.480; hospital staff with integrity as a dominant indicator for honesty, given the loading factor value at 0.825 and R2 value at 0.472.  Conclusion: Women’s customer trust of inpatient services in hospitals at West Java is in good condition. Honesty and benevolence dimension also has the same value in measuring women’s customer trust. The most dominant indicator in measuring the dimension of benevolence is hospital staff and hospital staff with integrity for the honesty dimension.Keywords: Customer trust, women, inpatient service, hospital.